Design and Development of Flash-Based Learning Media for Enhancing Students’ Learning Interest - Febby Rullya Rasyid; Tubagus Ali Rachman Puja Kesuma; Karsiwan (WISE Pendidikan Indonesia, 2025)
This study aimed to design and develop Flash-based learning media to enhance student engagement in sociology education at SMK Negeri 4 Bandar Lampung. The media was developed using the Cooperative Learning model, and its effectiveness was evaluated through expert assessments and field trials, following the Borg and Gall development steps. The results showed that the Flash-based media significantly increased student interest in learning compared to traditional PowerPoint presentations. The multimedia tool, integrating visual, auditory, and interactive elements, helped students better understand abstract sociological concepts. The findings indicate that Flash-based learning media is a promising tool for improving student motivation and learning outcomes in vocational high school settings. The study contributes to the growing body of research on multimedia applications in social science education and emphasizes the importance of integrating digital tools in classroom teaching to foster engagement and enhance learning experiences. The study’s limitations include a small sample size and the focus on short-term engagement. Future research should examine the long-term impact of such media on academic performance and explore its broader applicability across different educational contexts.